2003
DOI: 10.1046/j.1365-2648.2003.02633.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary health care provision for adults with a learning disability

Abstract: This study indicates a need for closer support and partnership with the learning disability service. The factors necessary for providing health care to people with learning disabilities extend beyond the domain of primary care teams. The findings of this survey have important implications for education and support to enable carers and professionals to provide a high standard of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 46 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Nineteen articles, published between 2004 and 2017, were included in this group (Table 14). Six of these studies dealt with GP services, 75,79,82,83,91 four dealt with a range of primary services, 74,77,78,84 three dealt with palliative or end-of-life care service, 86,88,90 two dealt with sexual health services, 81,85 two dealt with diabetes services, 73,89 one dealt with dental services 80 and one study dealt with non-specific cancers in this population. 87 The majority of these studies had a qualitative design, [73][74][75][76][77]80,82,83,85,87,89,90 a few had a cross-sectional study design 78,79,81,84,85,88,91 and one was a case study.…”
Section: Interaction During a Consultationmentioning
confidence: 99%
See 3 more Smart Citations
“…Nineteen articles, published between 2004 and 2017, were included in this group (Table 14). Six of these studies dealt with GP services, 75,79,82,83,91 four dealt with a range of primary services, 74,77,78,84 three dealt with palliative or end-of-life care service, 86,88,90 two dealt with sexual health services, 81,85 two dealt with diabetes services, 73,89 one dealt with dental services 80 and one study dealt with non-specific cancers in this population. 87 The majority of these studies had a qualitative design, [73][74][75][76][77]80,82,83,85,87,89,90 a few had a cross-sectional study design 78,79,81,84,85,88,91 and one was a case study.…”
Section: Interaction During a Consultationmentioning
confidence: 99%
“…Ten papers discussed issues around capacity for people with ID to give consent or make other decisions about their health care, 75,84,89 cervical screening, 78,84 sexual health, 85 contraception 81 and end-of-life care. [86][87][88]90 An ethnographic study 75 in which six people with ID were observed having a routine blood test in general practice found that information was not provided in an accessible format to support decisionmaking and that inconsistent levels of explanation were given for the procedure without checking for understanding.…”
Section: Support Capacity To Give Consentmentioning
confidence: 99%
See 2 more Smart Citations
“…Reasons for the neglect include lack of knowledge, misperceptions, and fear on the part of the provider (Krogman, ). Limited education concerning the needs of DS females contributes to neglect of health care (Elaine, ; Keywood & Flynn, ; Krogman, ). Social inclusion has implemented change in education and living arrangements for individuals with IDs but has done little for the problem of health care.…”
Section: Issue Of Concernmentioning
confidence: 99%